Description of the TETRA 1 technology and standard for modern digital trunking systems of functional mobile radio communications - Svrzić, Slađan M.; Jovanoski, Petar (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: Since the end of 1995, when TETRA MoU promoted the new TETRA Standard within ETSI, tentatively called TETRA 1, it quickly began to be used, almost exclusively, for the construction of Functional UHF digital trunking systems for mobile radio communications.Methods: A description of the relevant issues from the TETRA 1 technology standards and an analysis of existing specifications, with a more detailed presentation of the radio interface.Results: This article highlights the numerous advantages that radio systems based on the TETRA Standard have in relation to the Functional systems of analog trunking of mobile radio communications, and gives an overview of the basic package of Specifications for system implementation based on the TETRA Standard 1. It describes the interfaces used in the system with a special reference to the description of the radio interface, organized by TDMA, and the method of integration of voice and data transmission. The organization and the basic elements of the TETRA network infrastructure are presented as well as those of the final user's equipment, followed by the analysis of possible practical architectures of mobile radio communication networks based on that standard.Conclusion: After the general descriptions of technology, organization, and architecture, the following are presented: the basic concept of the organization of TETRA 1 network use, the general principle of organization of mobile participants' connections and the basic elements of the TETRA network as well as the architecture and topology of the TETRA 1 network construction.
Keywords: Mobile radio communications-MR; Professional Mobile Radio Communication System-PMR; analog trunking; digital trunking; TDMA; Radio-Air interface; Digital Trunking System of Mobile Radio Communications-TETRA; ETSI